The Economic Costs of Mass Surveillance: Insights from Stasi Spying in East Germany - Andreas Lichter; Max Loeffler; Sebastian Siegloch (Institute for the Study of Labor (IZA), 2015)
Based on official records from the former East German Ministry for State Security, we quantify the long-term costs of state surveillance on social capital and economic performance. Using county-level variation in the spy density in the 1980s, we exploit discontinuities at state borders to show that higher levels of Stasi surveillance led to lower levels of social capital as measured by interpersonal and institutional trust in post-reunification Germany. We estimate the economic costs of spying by applying a second identification strategy that accounts for county fixed effects. We find that a higher spy density caused lower self-employment rates, fewer patents per capita, higher unemployment rates and larger population losses throughout the 1990s and 2000s. Overall, our results suggest that the social and economic costs of state surveillance are large and persistent.
Keywords: H11; N34; N44; P26; 330; spying; surveillance; social capital; trust; East Germany